PEMBANGUNAN HUKUM YANG BERKEADILAN GENDER (Pendekatan Studi Hukum Kritis Bagi Perlindungan Hak Asasi Perempuan Di Indonesia Pasca Ratifikasi CEDAW) - Shinta Dewi Rismawati (MUWAZAH : jurnal kajian gender, 2011)
The ratification of the CEDAW Convention through Law No. 7 of 1984 has konesekuensi depth, because the “spirit” that convention should be followed up by making gender-just legal rules, in other words the state has a moral obligation and legal accountability to promote the protection, promotion and protection of human rights against women. In order to realize the mission, the critical legal studies approach can be used as a means to oversee efforts to protect Women Rights in Indonesia